2018
DOI: 10.1609/aaai.v32i1.11497
|View full text |Cite
|
Sign up to set email alerts
|

WiFi-Based Human Identification via Convex Tensor Shapelet Learning

Abstract: We propose AutoID, a human identification system that leverages the measurements from existing WiFi-enabled Internet of Things (IoT) devices and produces the identity estimation via a novel sparse representation learning technique. The key idea is to use the unique fine-grained gait patterns of each person revealed from the WiFi Channel State Information (CSI) measurements, technically referred to as shapelet signatures, as the "fingerprint" for human identification. For this purpose, a novel OpenWrt-based IoT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In contrast, by feeding a massive amount of data into machine learning [22] or deep learning networks, [9], [5], learning based achieve remarkable performances in complicated sensing tasks. Various deep neural networks are designed to enable many applications including activity recognition [23], gesture recognition [9], human identification [11], [12], [24], and people counting [13], [14]. Though deep learning models have a strong ability of function approximation, they require tremendous labeled data that is expensive to collect and suffer from the negative effect of distribution shift caused by environmental dynamics [25].…”
Section: Models and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, by feeding a massive amount of data into machine learning [22] or deep learning networks, [9], [5], learning based achieve remarkable performances in complicated sensing tasks. Various deep neural networks are designed to enable many applications including activity recognition [23], gesture recognition [9], human identification [11], [12], [24], and people counting [13], [14]. Though deep learning models have a strong ability of function approximation, they require tremendous labeled data that is expensive to collect and suffer from the negative effect of distribution shift caused by environmental dynamics [25].…”
Section: Models and Datamentioning
confidence: 99%
“…By analysing the patterns of its wireless signal, today's AP has evolved beyond a pure WiFi router, but is also widely used as a type of 'sensor device' to enable new services for human sensing. Particularly, recent studies have found that WiFi signals in the form of Channel State Information (CSI) [1], [2] are extremely promising for a variety of devicefree human sensing tasks, such as occupancy detection [3], activity recognition [4], [5], [6], [7], fall detection [8], gesture recognition [9], [10], human identification [11], [12], and people counting [13], [14]. Unlike the coarse-grained received signal strengths, WiFi CSI records more fine-grained information about how a signal propagates between WiFi J. Yang, X. Chen, D. Wang, H. Zou and L. Xie are with the School of Electrical and Electronics Engineering, Nanyang Technological University, Singapore (e-mail: {yang0478,dazhuo001,zouh0005,elhxie}@ntu.edu.sg).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gait recognition can be achieved by extracting these interrelated salient features. The advantage of gait-based human identification is that gait can not only be captured at a longer distance but is also difficult to imitate, which has attracted many researchers to employ various sensors for gait recognition [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate issues such as privacy and weak light, the researchers propose using WiFi for identity recognition, based on the principle that each person's unique body features and gait characteristics lead to different channel state information (CSI) patterns to recognize subtle differences between people [10]. [11] combines the convolutional layer with the LSTM layer and proposes a simple and effective deep learning method to realize automatic identification of people by WiFi.…”
Section: Introductionmentioning
confidence: 99%